Implementation of Religious Culture Through Mentoring in Elementary Schools - Fuadi, Shofa; Wuryandini, Endang; Muhtarom, Muhtarom (Jurnal Pendidikan (Teori dan Praktik), 2025)
The rapid development of globalization has influenced educational systems, requiring schools to strengthen character education. One effective approach to this effort is the implementation of religious culture through mentoring. This study aims to analyze how religious culture is implemented through mentoring at SD Negeri 05 Bojongbata. Using a qualitative descriptive design, data were collected through observation, interviews, and documentation. The findings show that mentoring plays a pivotal role in enhancing students’ religious character and discipline. The implementation of religious culture through mentoring at SD Negeri 05 Bojongbata includes five main activities: (1) Smile, regards, greet; (2) Reading the Qur’an; (3) Congregational prayer; (4) Commemoration of Islamic holidays; and (5) Collective prayer. The analysis indicates that structured mentoring significantly strengthens character education by internalizing religious values into students’ daily school life. This study provides a new model for integrating mentoring into religious culture programs to strengthen character education in public elementary schools, offering theoretical and practical implications for religious and moral education.